Искуствата на СР Германија во развојот на малите и средните претпријатија и на претприемништвото - Моцан, Перо (Економски факултет, УКИМ, Скопје, 2012)
The present doctoral thesis is an in-depth analysis of the experiences in the Federal Republic of Germany in the field of the development of Small and Medium Sized Enterprises and Entrepreneurship. The treatment of Small and Medium Sized Enterprises in the temporary German Entrepreneurship literature is based on the modern Anglo-Saxon Theory of Entrepreneurship. However, the German literature incorporates numerous features that derive from the German tradition – especially from the Freiburg Economic School and the model of the social market economy. The dissertation thoroughly follows the development of SMEs in Germany (total number of SMEs, their sectoral and regional structure and their contribution towards the creation of new workplaces) from the end of World War II up to date. The Federal Republic of Germany belongs to the list of countries that created complex policies for the promotion of SMEs and Entrepreneurship, including a large number of measures and instruments on all levels – European, Federal, Provincial and Local, with programmes that do mobilise enormous resources with significant efficacy. In this context, the promotional policies for SMEs in Germany are being analysed in detail – the role of the Federal and Provincial Governments, the anti-trust policies, the chambers of commerce, the State bank for SMEs (KfW Mittelstandsbank), the Universities, the risk capital and subcontracting. Based on that, the best practice experiences of the promotional policies for SMEs and Entrepreneurship in Germany have been selected. These can be of huge value for the promotional policies for SMEs and Entrepreneurship in the Republic of Macedonia.
The experience of the Federal Republic of Germany in the development of small and medium sized enterprises and entrepreneurship
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Таки Фити.
Keywords: SMEs, Entrepreneurship, German ordoliberalism, social market economy, promotional policies in Germany, business start-up, best practices, lessons for the Republic of Macedonia